Confucian educational canons and the reading culture of modern Chinese university students - Zhang, Ning (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The traditional Confucian educational canons (modifying education according to individual needs, education for all, combining education with enjoyment, enlightening and instructing, balancing learning, thinking and action, revisiting the past to discover the new) and their role in the development of students’ reading culture are considered. The reading culture of modern Chinese university students is analysed. Such strategies for improving students’ reading culture, as the use of Confucian pedagogical classics as models for the formation of skills of their interpretation in the context of cultural traditions and moral imperatives of Confucius’ teachings, the adaptation of Confucian educational canons to modern tasks of development of communicative technologies of education, are proposed and substantiated.